(untitled) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
Spodoptera litura is a pest that is polyphagous or can attack various types of plants, one of which is attacking cabbage plants. These pests can cause up to 90,00% damage if control measures are not taken. Therefore, to suppress the population of S. litura, control measures are needed. One alternative that can be done is by using pesticides made from plants, namely Noni Morinda citrifolia. The aim of the study was to determine the effect of noni fruit extract M. citrifolia on pests S. litura on cabbage plants. The study was conducted using a completely randomized design (CRD) with 5 treatments and 4 replications. Which consisted of 4 treatments using noni fruit extract and 1 control treatment. Concentration : 40,00% (40 ml extract + 60 ml aquadest), 50,00% (50 ml extract + 50 ml aquadest), 60,00% (60 ml extract + 40 ml aquadest) and 70,00% (70 ml extract + 30 ml aquadest). The results showed that the concentration of noni fruit extract M. citrifolia affected the mortality of S. litura pests on cabbage plants. Noni fruit extract concentration 40,00% was able to cause 22.50% mortality, 50,00% concentration was able to cause 30% mortality, 60,00% concentration was able to cause 40,00% mortality, and 70,00% concentration caused 50,00% mortality at 4 dap. The higher the concentration of noni fruit extract, the higher the mortality of S. litura on cabbage. Based on the results of research and discussion, it can be concluded that treatment with a concentration of 70,00% was able to cause mortality of 50,00% on day 4 after the application of noni fruit extract.